The Role and Responsibilities of the Military Police in Handling Criminal Acts of Fraud by Members (Case Study in Military Region IV/Diponegoro and Military Police Detachment IV/5) - Surorejo, Sudiyanto; Ngazis, Muhammad (UNISSULA Semarang, 2025)
Abstract. A case study in Military Region IV/Diponegoro shows the importance of Military Police professionalism in resolving legal violations firmly, fairly, and transparently. The aim of this research is to examine and analyze the role and responsibility of the military police in dealing with fraud crimes by members (Case Study in Military Region IV/Diponegoro and Military Police Detachment IV/5) and to identify obstacles in carrying out the role and responsibility of the military police in addressing fraud crimes by members (Case Study in Military Region IV/Diponegoro and Military Police Detachment IV/5) and how to overcome them. This study uses a sociological juridical method with descriptive-analytical specifications. Primary data were obtained directly through interviews and analyzed using legal theory. The results of this study concern the role and responsibility of the military police in handling fraud committed by members (Case Study in Military Region IV/Diponegoro and Military Police Detachment IV/5). The Military Police have a strategic role in handling fraud committed by TNI members, as regulated in Law Number 3 of 2025 concerning the Amendment to Law Number 34 of 2004 on the Indonesian National Armed Forces and Law Number 31 of 1997. In the case of Sertu NSW which occurred in the Kodam IV/Diponegoro area, Military Police Detachment IV/5 concerned an investigation based on Article 378 of the Criminal Code. The investigation process followed Article 75, including the summoning of witnesses, seizure of evidence, and detention. In handling fraud committed by TNI members, the Military Police face several obstacles, such as difficulty obtaining testimony from witnesses due to fear, and pressure from families to settle the case amicably. In the case of Sertu NSW, witnesses were reluctant to come to the Denpom, even though the loss amounted to IDR 114,700,000. Solutions to these problems include providing legal protection to witnesses according to the principle of witness and victim protection, educating all parties about criminal sanctions, and guaranteeing the confidentiality of witness identities so they are willing to provide honest testimony.